Technology-Based Interventions in Tobacco Use Treatment Among People Who Identify as African American/Black, Hispanic/Latina/o, and American Indian/Alaska Native: Scoping Review - Emily Hichborn; Avery Turner; Sarah Moore; Phoebe Gauthier; Kathleen Bell; LaTrice Montgomery; Jesse Boggis; Chantal Lambert-Harris; Elizabeth Saunders; Jesse Dallery; Bethany McLeman; Lisa Marsch (JMIR Publications, 2024)
BackgroundAlthough tobacco use has significantly declined in the general population, traditional tobacco use treatment uptake and success rates remain disproportionately low among people who identify as African American/Black, Hispanic/Latina/o, and American Indian/Alaska Native. Technology-based interventions (TBIs) for tobacco use are promising alternatives to traditional tobacco use treatments. ObjectiveThis scoping review aims to investigate the extent to which the use of digital TBIs in tobacco use treatment research promotes health equity among people who identify as African American/Black, Hispanic/Latina/o, and American Indian/Alaska Native. MethodsThis scoping review identifies US-based studies (between January 2000 and March 2021) that enlist TBIs for tobacco use treatment and include people who identify as African American/Black, Hispanic/Latina/o, and American Indian/Alaska Native at ≥50% of the sample when combined; features studies that are also race and ethnicity conscious; and highlights health equity-promoting insights from included studies. ResultsIn 85% (22/26) of the studies, the largest proportion of the sample was African American/Black, most participants had low socioeconomic status, and recruitment was most commonly from medical settings. In total, 58% (15/26) of the studies were race and ethnicity conscious, and 67% (10/15) of these studies sought to partner with potential end users. An array of TBIs were represented; however, SMS text messaging was most prevalent. Most TBIs were combined with other evidence-based intervention components (eg, nicotine replacement therapy). Approximately one-third of the studies (8/26, 31%) required participants to have their own device or internet access. The majority were underpowered to detect substantial differences. ConclusionsThe modest number of studies, particularly for persons who identify as Hispanic/Latina/o and American Indian/Alaska Native, demonstrates the limited application of TBIs for tobacco use and that additional research is needed to determine the extent to which TBIs for tobacco use promote health equity among these populations. International Registered Report Identifier (IRRID)RR2-10.2196/34508